LncRNA linc00312 suppresses radiotherapy resistance by targeting DNA-PKcs and impairing DNA damage repair in nasopharyngeal carcinoma - Guo, Zhen; Wang, You-Hong; Xu, Heng; Yuan, Chun-Su; Zhou, Hong-Hao; Huang, Wei-Hua; Wang, Hui; Zhang, Wei (Cell death & disease, 2021)
Radioresistance is the main obstacle in the clinical management of nasopharyngeal carcinoma (NPC). linc00312 is deregulated in a number of human cancers, including NPC. However, the detailed functions and underlying mechanisms of linc00312 in regulating radiosensitivity of NPC remains unknown. In this study, cox regression analysis was used to assess the association between linc00312 and NPC patients’ survival after radiotherapy. Our results reveal that linc00312 is significantly down-regulated in NPC tissues and patients with higher expression of linc00312 are significantly associated with longer overall survival and better short-term radiotherapy efficacy. Overexpression of linc00312 could increase the sensitivity of NPC cells to ionizing radiation, as indicated by clonogenic survival assay, comet assay, and flow cytometry. Mechanistically, RNA pull down and RNA immunoprecipitation were performed to investigate the binding proteins of linc00312. linc00312 directly binds to DNA-PKcs, hinders the recruitment of DNA-PKcs to Ku80, and inhibits phosphorylation of AKT–DNA–PKcs axis, therefore inhibiting the DNA damage signal sensation and transduction in the NHEJ repair pathway. In addition, linc00312 impairs DNA repair and cell cycle control by suppressing MRN–ATM–CHK2 signal and ATR–CHK1 signal. In summary, we identified DNA-PKcs as the binding protein of linc00312 and revealed a novel mechanism of linc00312 in the DNA damage response, providing evidence for a potential therapeutic strategy in NPC.